A companion to Greek architecture - Miles, Margaret M. (Chichester, West Sussex : Wiley, 2016)
A Companion to Greek Architecture provides an expansive overview of the topic, including design, engineering, and construction as well as theory, reception, and lasting impact. Covers both sacred and secular structures and complexes, with particular attention to architectural decoration, such as sculpture, interior design, floor mosaics, and wall painting Makes use of new research from computer-driven technologies, the study of inscriptions and archaeological evidence, and recently excavated buildings Brings together original scholarship from an esteemed group of archaeologists and art historians Presents the most up-to-date English language coverage of Greek architecture in several decades while also sketching out important areas and structures in need of further research
Keywords: Classical Greek Culture; Electronic books